Pengaruh Penerapan Buku Saku pada Pelatihan Keselamatan dan Kesehatan Kerja (K3) terhadap Hasil Belajar Kognitif pada UMKM Sambel Pecel Mahkota di Desa Ampel - Lintang Aura Berlianti; Mauren Gita Miranti; Nugrahani Astuti; Andika Kuncoro Widagdo (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study is a development research aimed at determining the effect of pocket book implementation as a training medium on improving workers’ knowledge of K3 at Sambel Pecel Mahkota Company in Ampel Village. The pocket book was designed as a concise, practical, and user-friendly learning medium to help workers understand OSH concepts, workplace risks, and safety procedures in daily work activities. This research employed a quantitative approach using a one-group pre-test post-test design and involved 10 workers as research participants. The results indicated a significant improvement in workers’ knowledge, with the average score increasing from 81.00 to 95.00. The pocket book had a statistically significant effect on improving OSH knowledge. The development of this pocket book went through several stages, including needs analysis, material design, expert validation, and field trials. The content covers hazard identification, use of personal protective equipment, emergency procedures, and basic ergonomics relevant to food production environments. These findings suggest that pocket books are an effective and accessible training tool, particularly for small-scale industries with limited resources, and can be recommended as a practical intervention to strengthen workplace safety culture.